Affective picture processing is modulated by emotion word type in masked priming paradigm: an event-related potential study. Issue 3 (2nd April 2020) - Wu, Chenggang; Zhang, Juan; Yuan, Zhen
ABSTRACT: Although a large body of research demonstrates the role of language in emotion processing (e.g. emotional facial expressions), how emotion-laden words (e.g. poison, reward) and emotion-label words (e.g. fear, satisfaction) differently impact affective picture processing is not clear. Emotion-label words label affective states straightforwardly, whereas emotion-laden words engender emotion via reflection. The current study adopted the masked priming paradigm to examine how Chinese emotion-laden words and emotion-label words distinctively influence affective picture processing. Twenty Chinese speakers decided the valence of the pictures with their cortical responses recorded. Emotion-label words facilitated affective picture evaluation behaviourally. Moreover, pictures that were preceded by emotion-laden words generated larger electrophysiological activation than those preceded by emotion-label words. Combined behavioural and ERP evidence revealed that emotion word type modulated affective picture processing, suggesting different roles of emotion-laden and emotion-label words in how emotion is shaped by language.